2020
DOI: 10.2147/ijgm.s285833
|View full text |Cite
|
Sign up to set email alerts
|

<p>Cushing’s Disease Caused by a Pituitary Microadenoma Coexistent with a Meningioma: A Case Report and Literature Review</p>

Abstract: Cushing's disease (CD), also known as adrenocorticotropic hormone (ACTH)dependent pituitary Cushing's syndrome, is a rare and serious chronic endocrine disease that is usually caused by a pituitary adenoma (especially a pituitary microadenoma). Meningioma is the most common type of primary intracranial tumor and is usually benign. The patient in this case report presented with CD coexisting with pituitary microadenoma and meningioma, which is an extremely rare comorbidity. The pathogenesis of CD associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…ACTH secreting pituitary adenomas though very rare (incidence of 1-2 per million) are responsible for 70 % of all endogenous causes of Cushing's syndrome. 11,18 However our patient's Brain MRI was normal. Our patient developed Cushing's syndrome secondary to oral corticosteroid-prednisolone abuse.…”
Section: Discussionmentioning
confidence: 59%
“…ACTH secreting pituitary adenomas though very rare (incidence of 1-2 per million) are responsible for 70 % of all endogenous causes of Cushing's syndrome. 11,18 However our patient's Brain MRI was normal. Our patient developed Cushing's syndrome secondary to oral corticosteroid-prednisolone abuse.…”
Section: Discussionmentioning
confidence: 59%
“…The results showed that the largest percentage according to Lab Results was in favor of High with a rate of 86 and a percentage of (84.30%), followed by Low with a rate of 13 and a percentage of (12.70 %), and followed by normal with a rate of 3 and a percentage of (2.90 %) Microadenoma is a benign tumor that originates in the pituitary gland, a pea-sized organ behind the eyes that controls growth, development, metabolism, and reproduction. Microadenomas can be functional (producing hormones) or nonfunctional (not producing hormones) [15].…”
Section: Resultsmentioning
confidence: 99%
“…The subject of impairments in ACTH-cortisol axis in meningioma patients was not under particular scientific consideration yet. This topic in scientific literature is usually considered in context of meningioma and pituitary adenoma coexistence -which may result with Cushing disease [10]. On the other hand, rapid growth of meningioma, may result up with hypoglycemia [11].…”
Section: State Of the Artmentioning
confidence: 99%